ChemInform Abstract: Bi2Fe4O9: Structural Changes from Nano‐ to Micro‐Crystalline State. Issue 32 (22nd July 2016) - Kirsch, Andrea; Murshed, M. Mangir; Gaczynski, Piotr; Becker, Klaus‐Dieter; Gesing, Thorsten M.
Abstract: Nanocrystalline Bi2 Fe4 O9 is prepared by the polyol‐mediated reaction of Bi(NO3 )3, Fe(NO3 )3, and NaOH (1:2:4) in diethylene glycol (423 K, 2.5 h) after which stearic acid is added.